Inflammatory mediators of neuropathic pain - José Oswaldo de Oliveira Júnior; Caio Sander Andrade Portella Junior; Cláudia Panossian Cohen (Revista Dor)
ABSTRACT BACKGROUND AND OBJECTIVES: Pro-inflammatory chemical mediators and algogenic substances seem to be confused by the sharing of their actions and by interactions in painful and inflammatory presentation. This study aimed at presenting a review of major inflammatory chemical mediators and place them in neuropathic pain pathophysiology. CONTENTS: Inflammation is the homeostatic response of vascularized tissues to remove harmful agents and restore their normal functions. Nervous system (central and/or peripheral) diseases and injuries may induce neuropathic pain and may also modify inflammatory process nervous mediation. In such pathological conditions, there might be pain without restrict link with admitedly harmful or painful stimuli, as well as there might be inflammation without restrict link with the presence of harmful agents and the need to remove them. Chemical mediators involved in neuropathic pain and inflammation pathophysiology modulate the presentation of both. CONCLUSION: Studies on inflammation offer evidences to support the important role of their chemical mediators in neuropathic pain pathogenesis. In peripheral and central sensitization, a thin borderline between reversibility or not of neuropathic pain may be respected or exceeded by inflammatory mediators actions.